2(1H)-Pyridone and Quinolone as Synthon for Efficient and Simple Synthesis of Polysubstituted Pyridines and Quinolines. (2nd January 2023) - Ali, Samar Mosad Mohamed; Salem, Marwa S.; Madkour, Hassan M. F.; Zidan, Alaa
Abstract: The authors aimed at utilize a facile one-pot multicomponents reaction to construct a variety of heterocyclic systems namely, 2-oxo-hexahydroquinoline, pyrazolo[3, 4- b ]pyridine and 2-oxo-1, 2-dihydropyridine-3-carbonitrile derivatives which were used as a scaffold for the synthesis of many fused heterocyclic systems namely, thieno[2, 3- b ]quinoline, tetrazolo[1, 5- a ]quinoline, and hexahydro-[1, 2, 4]triazolo[1, 5- a ]quinoline derivatives, as well as non-fused heterocyclic systems such as tetrahydroquinoline, hexahydroquinoline, nicotinonitrile, and nicotinamide derivatives. The structures assigned for new compounds were confirmed by microanalytical and spectral data.